Analisis Perbedaan Kinerja Keuangan atas Penerapan Pajak Penghasilan Final dan Nonfinal (Studi pada Perusahaan Jasa Konstruksi di Bursa Efek Indonesia) - , Yoke Feriyanto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Construction service business is business activity that provides planning consultation, supervision consultation, and construction work implementation. Construction service business income is currently subjected to the Final Income Tax. Previously, however, construction service net income is subject to the Nonfinal Income Tax. The Final and Nonfinal Income Tax regulation is affecting the financial performance of construction service companies which is measured by the Economic Value Added (EVA). Therefore, this research aims to observe whether there is a difference between the EVA resulting from the Final Income Tax and the EVA resulting from the Nonfinal Income Tax. The type of this research is descriptive statistic and hypothesis testing. Three construction service companies listed in the Indonesian Stock Exchange are selected as the research samples as follow: PT. Adhi Karya (Persero) Tbk. (ADHI), PT. Surya Semesta Internusa Tbk. (SSIA), and PT. Total Bangun Persada Tbk. (TOTL). The data collection methods used are collection method and analysis of secondary data published from 2006 to 2010 (record analysis). The analaysis methods used are profitability ratio analysis method, descriptive statistics, EVA method, and comparative analysis using paired two samples for means t-test. The hypothesis of this research is whether or not there is a difference in EVA resulting from the applications of Final and Non Final Income Tax. Based on the analysis result, the following conclusions can be made: (1) there are differences on Economic Value Added from Final and Nonfinal Income Tax implementation. The Economic Value Added from Final Income Tax implementation is lower than the Nonfinal Income Tax implementation. There are two factors causing smaller EVAf than EVAnf: firstly is NOPATf value is lower than NOPATnf value